Identification of neurovascular changes associated with cerebral amyloid angiopathy from subject-specific hemodynamic response functions. Issue 10 (October 2017) - Williams, Rebecca J; Goodyear, Bradley G; Peca, Stefano; McCreary, Cheryl R; Frayne, Richard; Smith, Eric E; Pike, G Bruce
Cerebral amyloid angiopathy (CAA) is a small-vessel disease preferentially affecting posterior brain regions. Recent evidence has demonstrated the efficacy of functional MRI in detecting CAA-related neurovascular injury, however, it is unknown whether such perturbations are associated with changes in the hemodynamic response function (HRF). Here we estimated HRFs from two different brain regions from block design activation data, in light of recent findings demonstrating how block designs can accurately reflect HRF parameter estimates while maximizing signal detection. Patients with a diagnosis of probable CAA and healthy controls performed motor and visual stimulation tasks. Time-to-peak (TTP), full-width at half-maximum (FWHM), and area under the curve (AUC) of the estimated HRFs were compared between groups and to MRI features associated with CAA including cerebral microbleed (CMB) count. Motor HRFs in CAA patients showed significantly wider FWHM ( P  = 0.006) and delayed TTP ( P  = 0.03) compared to controls. In the patient group, visual HRF FWHM was positively associated with CMB count ( P  = 0.03). These findings indicate that hemodynamic abnormalities in patients with CAA may be reflected in HRFs estimated from block designs across different brain regions. Moreover, visual FWHM may be linked to structural MR indications associated with CAA.